PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN RETURN ON ASSET (ROA) TERHADAP RETURN SAHAM PADA BANK - Aulia, Junda Nur; Kusno, Hendra Sanjaya; Ghozi, Saiful (Manajemen & Bisnis Jurnal, 2021)
This study goals to determine the effect of current ratio (CR), debt-to-equity ratio (DER) and return on belongings (ROA) on return on equity. owned at conventional banks listed on the Indonesian Stock Exchange throughout the period 201 -2020 The facts used in this learn about is taken from the annual document posted by way of the Indonesia Stock Exchange (IDX) for duration 201 -2020. The analytical method used is a couple of linear regression evaluation to determine the affect of the unbiased variable on the based variable. The sample measurement used to be determined the use of the rational sampling method and the pattern used in this find out about was only 20 traditional banks. The results of this study furnish empirical proof that cutting-edge ratio (CR), debt ratio (DER) and return on assets (ROA) have an effect on inventory returns. Then, the effects of this learn about show that modern-day ratio (CR) has no impact on inventory returns, debt-to-equity ratio (DER) has a positive and good sized effect on stock returns. stock returns and return on assets (ROA) have a positive and widespread effect on return on equity.